2013
DOI: 10.1111/evo.12207
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Fitness Landscapes in Response to Altered Environments

Abstract: The role of adaptation in molecular evolution has been contentious for decades. Here, we shed light on the adaptive potential in Saccharomyces cerevisiae by presenting systematic fitness measurements for all possible point mutations in a region of Hsp90 under four environmental conditions. Under elevated salinity, we observe numerous beneficial mutations with growth advantages up to 7% relative to the wild type. All of these beneficial mutations were observed to be associated with high costs of adaptation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
145
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 51 publications
12
145
3
Order By: Relevance
“…In a recent evaluation of the distribution of fitness effects (DFE) in both the presence and absence of antibiotic in the bacterium Pseudomonas fluorescens, Kassen and Bataillon 18 found that of the 665 resistance mutations isolated, greater than 95% were deleterious in the absence of the antibiotic treatment. In populations of yeast raised in both standard and challenging environments (in this case, high temperature and high salinity), Hietpas et al 19 identified a handful of beneficial mutations in each of the challenge environments, all of which were deleterious under standard conditions, with some even being lethal in the absence of the selective pressure. Foll et al 20 in investigating the evolution of oseltamivir resistance mutations in the influenza A virus, identified 11 candidate resistance mutations, with the one functionally validated mutation (H274Y) having been demonstrated to be deleterious in the absence of drug pressure (see also refs 21,22).…”
Section: Nature Communications | Doi: 101038/ncomms6281mentioning
confidence: 99%
“…In a recent evaluation of the distribution of fitness effects (DFE) in both the presence and absence of antibiotic in the bacterium Pseudomonas fluorescens, Kassen and Bataillon 18 found that of the 665 resistance mutations isolated, greater than 95% were deleterious in the absence of the antibiotic treatment. In populations of yeast raised in both standard and challenging environments (in this case, high temperature and high salinity), Hietpas et al 19 identified a handful of beneficial mutations in each of the challenge environments, all of which were deleterious under standard conditions, with some even being lethal in the absence of the selective pressure. Foll et al 20 in investigating the evolution of oseltamivir resistance mutations in the influenza A virus, identified 11 candidate resistance mutations, with the one functionally validated mutation (H274Y) having been demonstrated to be deleterious in the absence of drug pressure (see also refs 21,22).…”
Section: Nature Communications | Doi: 101038/ncomms6281mentioning
confidence: 99%
“…Bulk competitions where many hundreds or thousands of mutations are analyzed in the same physical sample ensure that each mutation experiences equivalent experimental conditions, which facilitate precise measurements of the effects of each mutation (Hietpas et al 2013b). Mutations in genes that impact cooperation among individuals often lead to distinct physiological impacts in monoculture vs. bulk cultures.…”
Section: Quantification Of Local Mutational Landscapes Using Sequencimentioning
confidence: 99%
“…In addition to environmental conditions, experimental reproducibility of bulk competitions depends on many factors, including counting robustness (e.g., due to sequencing depth) and population management (e.g., bottlenecks where population size approaches mutational diversity will lead to stochastic frequency changes from random sampling). With careful attention to these issues (Hietpas et al 2013a), full experimental repeats of bulk competitions monitored by sequencing exhibit strong reproducibility and are capable of distinguishing functional effects on the order of 0.1% (Hietpas et al 2013b;Bank et al 2014).…”
Section: Quantification Of Local Mutational Landscapes Using Sequencimentioning
confidence: 99%
“…The effects of mutation may also depend on environmental conditions. Whether a mutation is neutral, beneficial, or deleterious can vary across spatial and temporal environments or with environmental quality (Hietpas, Bank, Jensen, & Bolon, 2013; Kraemer, Morgan, Ness, Keightley, & Colegrave, 2016; Latta et al., 2015; Martin & Lenormand, 2006, 2015). Unfortunately, except for a very few studies (Roles & Conner, 2008; Roles, Rutter, Dworkin, Fenster, & Conner, 2016; Rutter, Shaw, & Fenster, 2010; Rutter et al., 2012) we have a relatively poor understanding of the effect of mutation on fitness under natural conditions and thus few direct measures of the temporal and spatial variability in mutation rates and effects outside of the laboratory.…”
Section: Introductionmentioning
confidence: 99%